2012
DOI: 10.1111/j.1095-8649.2012.03399.x
|View full text |Cite
|
Sign up to set email alerts
|

The utility of a long‐term acoustic recording system for detecting white seabass Atractoscion nobilis spawning sounds

Abstract: This study reports the use of a long-term acoustic recording system (LARS) to remotely monitor white seabass Atractoscion nobilis spawning sounds at three sites along the southern California coastline, adjacent to Camp Pendleton. On the basis of previous studies of A. nobilis sound production relative to periods of known spawning activity, LARS were set to continuously record ambient sounds for a 2 h period around sunset from April to June 2009. Acoustic analyses identified A. nobilis courtship sounds on 89, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Collectively, a mean displacement of 229 km from the initial tagging location indicates that white seabass are capable of extensive seasonal migrations. Widespread horizontal movements during the spawning season are consistent with recent data that indicate limited residency periods at distinct spawning sites along the southern coast of California (Aalbers and Sepulveda, 2012). The broad movements docu-mented in our study contrast with the limited home ranges that have been observed in other coastal fishes (Holland et al, 1996;Lowe et al, 2003;Neat et al, 2006).…”
Section: Horizontal Movementssupporting
confidence: 91%
“…Collectively, a mean displacement of 229 km from the initial tagging location indicates that white seabass are capable of extensive seasonal migrations. Widespread horizontal movements during the spawning season are consistent with recent data that indicate limited residency periods at distinct spawning sites along the southern coast of California (Aalbers and Sepulveda, 2012). The broad movements docu-mented in our study contrast with the limited home ranges that have been observed in other coastal fishes (Holland et al, 1996;Lowe et al, 2003;Neat et al, 2006).…”
Section: Horizontal Movementssupporting
confidence: 91%
“…Many fishes of the family Sciaenidae are known to make sounds (Ramcharitar et al , ). The presence of sciaenid species of commercial interest has been investigated through passive acoustic monitoring (PAM), especially along the northern American coast (Rountree et al , ; Fine & Thorson, ; Luczkovich et al , ; Mann et al , ; Aalbers & Sepulveda, ). In the Mediterranean Sea, there are five different species of sciaenids.…”
Section: Statistical Comparisons Of the Acoustic Features Of Sounds Pmentioning
confidence: 99%
“…Long-term PAM is used to study decadal trends in the occurrence and distribution shifts of marine mammals (Van Parijs et al 2009, Davis et al 2017 and is increasingly being used to monitor fish occurrence and behavior (Locascio & Mann 2008, Mann et al 2009, Širović et al 2009, Nelson et al 2011, Aalbers & Sepulveda 2012, Bolgan et al 2018, Zemeckis et al 2019. Calling activity has been linked to reproductive behavior in many other fishes, including pomacentrids (Mann & Lobel 1995), batra choidids (McKibben & Bass 1998), sciaenids (Locascio & Mann 2008), and serranids (Rowell et al 2015).…”
Section: Introductionmentioning
confidence: 99%